On the Ambivalence of Recognition - Laitinen, Arto (Itinerari, 2023)
In this article I address the idea that recognition is fundamentally ambivalent: not only can there be bad forms of recognition – misrecognition, nonrecognition, disrespect – but that even the good or adequate forms of recognition may in some ways be detrimental to the recipient or sustain societal domination (Ikäheimo, Lepold, Stahl 2021). One version of the challenge is that social movements do better by focusing on other concepts than recognition, for their progressive aims. I will discuss the non-consequentialist nature of adequacy of recognition, value pluralism, the rewards of submissiveness, dialectical progression to adequate recognition, and “ambivalence of being” as providing partial explanations for the ambivalence of recognition, while arguing that adequate recognition is only contingently ambivalent. By discussing these challenges, I continue to articulate a conception of mutual recognition and misrecognition that I have developed earlier (Laitinen 2002, 2003, 2010, 2012, Ikäheimo & Laitinen 2007).